Analisis Nilai Ukhuwah Basyariyah dalam Fenomena War Takjil di Bulan Ramadhan - Ridho Egi Adi Saputra; Evi Dwi Septiani; Usmadina Aulia Rahman; Rio Kurniawan (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2025)
This research identifies and analyzes the values of Basyariah's brotherhood in the phenomenon of War Takjil, which occurs during Ramadan in Indonesia. This research uses a qualitative approach by observing and analyzing in-depth descriptive data. Using the literature review method, relevant data will be collected and analyzed. The results of the phenomenon research War Takjil are values of Basyariah brotherhood seen in individual and group activities to get takjil in Ramadan.Â